Ptenidium pusillum (Gyllenhal, 1808) from egg to pupa (Coleoptera: Ptiliidae) - Jałoszyński, Paweł (Zootaxa, 2015)
Eggs, larvae and pupae of Ptenidium pusillum obtained by rearing adults are described. Larval chaetotaxy is treated in detail. Two larval instars are identified, differing in minor chaetotaxic characters, pigmentation and measurements. The lack of urogomphi, confirmed in Ptenidium, is discussed in the context of current systematics of Ptiliidae. Serial chaetotaxic homology and between-instar homology are discussed. Observations related to biology of P. pusillum and associations with phoretic mites and nematodes are given.